2020
DOI: 10.5430/ijhe.v9n6p307
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Habits Appear Captured by WhatsApp

Abstract: Exploring students’ habits of using WhatsApp is important: such introspection helps students to reflect, and improve their actions. Habits are subconscious thoughts that drive students, for example, to use WhatsApp, even without concentrating on their learning actions. Habits are formed after students have repeated the same action. Twelve students, registered for a Bachelor of Education degree in Mathematics Education at a university in South Africa, were selected to participate. The objective of this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 33 publications
(45 reference statements)
0
24
0
1
Order By: Relevance
“…For example, in 2009, when WhatsApp was introduced by Jan Koum and Brian Acton (erstwhile Yahoo employees) for Smartphone communication, teachers saw a teaching and learning resource to be used for educational activities. The two leading SMSs (Facebook, and YouTube) also attracted many teachers when they were introduced (Khoza & Mpungose, 2020 ; Khoza, 2020b ). The SMSs are used as a teaching and learning resource which is defined as any object or person that communicates education (Khoza & Biyela, 2020 ).…”
Section: Societal Identitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in 2009, when WhatsApp was introduced by Jan Koum and Brian Acton (erstwhile Yahoo employees) for Smartphone communication, teachers saw a teaching and learning resource to be used for educational activities. The two leading SMSs (Facebook, and YouTube) also attracted many teachers when they were introduced (Khoza & Mpungose, 2020 ; Khoza, 2020b ). The SMSs are used as a teaching and learning resource which is defined as any object or person that communicates education (Khoza & Biyela, 2020 ).…”
Section: Societal Identitiesmentioning
confidence: 99%
“…This hints that, although the majority of participants had missed aims as the long term-goals of personal identity, P1, P2, and P6 had weblogs and WhatsApp to represent elements of personal identity. This identity is observed through habitual actions when humans engage their life activities (Czerniewicz & Brown, 2014 ; Khoza, 2020b ). However, P6, supported by P1, P2, and P8 indicated that he was driven by natural identity more than professional, societal, or personal identity.…”
Section: Theme 3: Personal Identitymentioning
confidence: 99%
“…Facebook and WhatsApp were examples of SMSs used by UKZN staff and students to communicate what they were doing. These two SMSs are among the most popular [7]. Staff and students had their personal and/or UKZN Facebook pages that they used for social and/or professional activities [4].…”
Section: Facebook and Whatsappmentioning
confidence: 99%
“…For example, ZVCT, which was launched in 2013, was founded in 2011 by Chinese-American businessman Eric S. Yuan in California for business meetings and conferences, not for formal education. In 2009, WhatsApp was introduced by Jan Koum and Brian Acton as a communication resource for Smartphone and other mobile phone users, not for formal education [7]. As a result, these resources are driven by societal identities that may be understood through formative assessment [5,13].…”
Section: Aimsmentioning
confidence: 99%
See 1 more Smart Citation